(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The average citizen expected that the businesses, which largely thrived on black money such as luxury goods, real estate and jewellery, will be hit by the demonetization move. But what is less understood is the impact of this move on the rural economy. Most, if not all, of the rural economy runs on cash and with wages hitting the Rs. 300-400 mark in many rural areas, Rs. 500 and Rs. 1,000 notes were an integral part of the rural economy. If it was just a matter of exchanging old notes for new notes, there would not have been so much inconvenience and the economy would not have been affected. But the culprit in the demonetization exercise has been its timing i.e. just after the harvesting season and also the limit on the amount that citizens could withdraw for the few weeks after the announcement. It has seen a lot of flip-flops since the announcement, but the end result of the move has been a sudden withdrawal of liquidity from the system. This descriptive study brings out the short term and long term as well as the severe and small impact on the rural poor of Madhya Pradesh who were the major victim of the cash crunch.